2015
DOI: 10.1093/ndt/gfv325
|View full text |Cite
|
Sign up to set email alerts
|

Collagen (COL4A) mutations are the most frequent mutations underlying adult focal segmental glomerulosclerosis

Abstract: We show that collagen IV mutations, including COL4A5, frequently underlie FSGS and should be considered, particularly with a positive family history. Targeted NGS improves diagnostic efficiency by investigating many candidate genes in parallel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
214
1
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 232 publications
(234 citation statements)
references
References 58 publications
10
214
1
9
Order By: Relevance
“…By far, the most common example of this is the newly identified association with APOL1 as discussed below. Other genetic risk loci include PDSS1 (71) and numerous others (72,73). More are likely to be discovered in the near future.…”
Section: Genetic Fsgsmentioning
confidence: 99%
“…By far, the most common example of this is the newly identified association with APOL1 as discussed below. Other genetic risk loci include PDSS1 (71) and numerous others (72,73). More are likely to be discovered in the near future.…”
Section: Genetic Fsgsmentioning
confidence: 99%
“…Nearly 100% of patients with congenital onset and 44% with infantile onset of NS have podocyte gene mutations, and the overall mutation detection rate is as high as 52% in steroid-resistant pediatric NS patients (3). The leading mutated podocyte genes include laminin β2 (LAMB2) causing congenital NS and Pierson syndrome and collagen IV α chain (COL4A) underlying Alport syndrome (AS) and focal segmental glomerulosclerosis (FSGS) (4). Emerging evidence has demonstrated that podocyte ER stress may be an important functional link from genetic mutations to disease phenotype in primary NS.…”
Section: Introductionmentioning
confidence: 99%
“…One mother showed focal segmental glomerulosclerosis (FSGS) on kidney biopsy. Presentation of Alport syndrome with isolated proteinuria [17] and FSGS in male and female patients [18][19][20][21] have been reported before. The etiology of FSGS may be that it develops secondary to the abnormalities in the GBM, or alternatively that FSGS belongs to a spectrum of diseases of the GBM primarily caused by a COL4A3-5 mutation.…”
Section: Discussionmentioning
confidence: 99%